Awareness rate of Ardabil city people about multiple sclerosis - Amani, Firouz; Hoseinzadeh, Shahnaz; Sabzvari, Ahmad; Avesta, Leili; Kahnamouei-Aghdam, Fariba; Barak, Manouchehr (International Journal of Advances in Medicine, 2017)
Background: Multiple Sclerosis (MS) is a chronic autoimmune disease of the central nervous system (brain and spinal cord) and affects the optic nerves. The aim of this study was to evaluate the knowledge rate of Ardabil city people about multiple sclerosis. Methods: This study is a descriptive analytical study that has been done on 150 people of Ardabil which selected randomly from all over the city based on geographical location. Data gathered by a questionnaire include two section characterized and knowledge questions. Collected data analyzed by statistical methods in SPSS.16 using tables, charts and statistical indexes. Results: The study population aged between 20-65 years with a mean age of 32/34 years. 48/7% of participants were female and 51/3% men. Approximately 25/3% of Participants in this study had good knowledge about MS and other have moderate level and lower rate of knowledge. Most of people get their information through TV and radio programs about MS (46/2%). Conclusions: Results showed that the knowledge rate of people about MS was in moderate and lower levels. So, present educational programs and increasing knowledge rate of people about MS by TV and radio programs is necessary.